Islamic Education Approach in Addressing Cyberbullying Among Adolescents - Zaenal Mukarom; Mubiar Agustin; Rohman Heryana; Laesti Nurishlah; Imron Heriyanto; Mochammad Ramdan Samadi (Edumaspul: Jurnal Pendidikan, 2023)
Cyberbullying is one of the big challenges faced by teenagers in today's digital era. This issue can have a negative impact on the mental, emotional, and social health of adolescents. This study aims to explore the approach of Islamic education in dealing with the issue of cyberbullying among adolescents. Through a qualitative method with a literature study approach, this study finds that the values and principles in Islamic education, such as manners, noble morals, and social responsibility, can be a strong foundation to prevent and overcome cyberbullying behavior. Islamic education emphasizes the importance of maintaining the honor of oneself and others and encouraging the wise use of technology. The results of this study are expected to contribute to the development of more effective educational strategies in tackling cyberbullying among adolescents, by utilizing Islamic values as the basis for the approach.